Kanohi ki te kanohi : a journey towards repatriation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Māori Studies at Massey University, Palmerston North, New Zealand - Tipene-Hook, Brenda (Massey University, 2011)
This thesis explores and examines Ngāti Hine perspectives with respect to taonga. Whilst past research has tended to focus on how museums have responded to international and domestic pressure in terms of their recognition of indigenous rights and cultural awareness, in contrast, the Ngāti Hine experience and the Ngāti Hine response is emphasised. With particular regard to the Ngāti Hine taonga tapu currently housed at the Auckland Museum, this thesis examines hapū-museum relationships from the perspective of Ngāti Hine and investigates and analyses the degree and quality of hapu-museum interaction. An account of the journey, thus far, that Ngāti Hine have made in terms of repatriating their taonga tapu back to within their tribal boundaries and jurisdiction is given. The Ngāti Hine experience is central to the research findings and shows how this journey continues to shape the current perspectives of Ngāti Hine in terms of their response to, and their relationship with, museums. The research consulted with participants drawn from within Ngāti Hine. Research methodology included one-to-one interviews, a focus group discussion, and a review of relevant literature. Appropriate and relevant methodologies for Māori-centred research, and in particular, Action Research methodology, were employed. Due to the nature of the research and the researcher’s personal cultural views and convictions, the Māori research participants were limited to those of Ngāti Hine descent who are known personally to the author. In addition, all interviews, consents, and dissemination of information complied with legislation regarding privacy and included any additional restrictions, or freedoms, stipulated by the participants. The expected timeframe was from November 2004 to January 2006 but was extended to August 2010. Whilst the research data has not been affected, some updates to the research have been made. Envisaged outcomes include the opportunity for Ngāti Hine to share their perspective in an area where they are infrequently consulted and to share their journey through the repatriation process. It is also hoped that this thesis will provide a better understanding of the hapū-museum dynamic and therefore assist in improving iwi/hapū-museum relationships.
Keywords: Ngāti Hine; Cultural property; Maori antiquities; Museum collections; Taonga tapu; Repatriation of cultural property; Hapu-museum relationships